2016
DOI: 10.1097/ijg.0000000000000282
|View full text |Cite
|
Sign up to set email alerts
|

Selective Laser Trabeculoplasty in Primary Angle-closure Glaucoma After Laser Peripheral Iridotomy

Abstract: The safety and efficacy of SLT was equivalent in PAC/PACG and POAG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 18 publications
1
24
0
3
Order By: Relevance
“…Studies involving the use of ALT and SLT in cases of angle closure have demonstrated efficacy when these methods are associated with previous procedures promoting a greater exposure of the TM such as peripheral iridotomy . Although a direct relationship can be established between the structural changes induced by ALT in the TM, involving enhanced aqueous humour outflow, and reduction of the IOP, similar correlations cannot be easily established with SLT although the effect is similar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies involving the use of ALT and SLT in cases of angle closure have demonstrated efficacy when these methods are associated with previous procedures promoting a greater exposure of the TM such as peripheral iridotomy . Although a direct relationship can be established between the structural changes induced by ALT in the TM, involving enhanced aqueous humour outflow, and reduction of the IOP, similar correlations cannot be easily established with SLT although the effect is similar.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the few studies available, both ALT and, more recently, SLT may be considered a new therapeutic option for the reduction of IOP in patients with different signs and symptoms of PACG showing more than 90° of visible pigmented TM before or after peripheral iridotomy . Within this context, SLT shows similar efficacy and a lower risk of complications because it tends to cause lower levels of secondary inflammation .…”
Section: Discussionmentioning
confidence: 99%
“…In patients who had controlled IOP of PAC/PACG under medication but were intolerant of the medications, SLT achieved a reduction of 1.6 medications. The success rate of SLT in reducing IOP by at least 20% was 84.7% in the PAC/PACG group, and the clinical outcomes were comparable to those in the POAG group [15]. …”
Section: Indications and Efficacymentioning
confidence: 99%
“…In the majority of these, an increase in IOP was detected only on the day of the SLT procedure and was controlled by medications and not considered a long-term complication. Roughly 2–26.2% of glaucoma patients experienced a temporary postoperative IOP spike [15, 16, 22, 34]. In Ali Aljasim et al’s study, an IOP spike of 10 mmHg was detected in 10% of PAC/PACG patients and 5% of POAG patients 1 h after the procedure [15].…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation